Cybersafety in Modern Online Social Networks - Blackburn, Jeremy; De Cristofaro, Emiliano; Sirivianos, Michael; Strufe, Thorsten (My University, 2017)
This report documents the program and the outcomes of Dagstuhl Seminar 17372 “Cybersafety in Modern Online Social Networks.” The main motivation behind the seminar stems from the increased relevance of threats and challenges in the context of cybersafety, especially in modern online social networks, where the range of malicious activities perpetrated by malevolent actors is regrettably wide. These include spreading malware and spam, controlling and operating fake/compromised accounts, artificially manipulating the reputation of accounts and pages, and spreading false information as well as terrorist propaganda.The reasons for the success of such attacks are manifold. The users of social networking services tend to extend their trust of the services and profiles of their acquaintances to unknown users and other third parties: despite the service providers’ attempts at keeping their audiences identifiable and accountable, creating a fake profile, also in another person’s name, is very simple. Even partially or fully taking over a profile is comparatively easy, and comes with the benefit of the trust this profile has accrued over time, as many credentials are easy to acquire. Further, even seemingly innocuous issues such as the design and presentation of user interfaces can result in implications for cybersafety. The failure to understand the interfaces and ramifications of certain online actions can lead to extensive over-sharing. Even the limited information of partial profiles may be sufficient for abuse by inference on specific features only. This is especially worrisome for new or younger users of a system that might unknowingly expose information or have unwanted interactions simply due to not fully understanding the platform they are using. Unfortunately, research in cybersafety has looked at the various sub-problems in isolation, almost exclusively relying on algorithms aimed at detecting malicious accounts that act similarly, or analyzing specific lingual patterns. This ultimately yields a cat-and-mouse game, mostly played on economic grounds, whereby social network operators attempt to make it more and more costly for fraudsters to evade detection, which unfortunately tends to fail to measure and address the impact of safety threats from the point of view of regular individuals. This prompts the need for a multi-faceted, multi-disciplinary, holistic approach to advancing the state of knowledge on cybersafety in online social networks, and the ways in which it can be researched and protected. Ultimately, we want to work towards development of a cutting-edge research agenda and technical roadmap that will allow the community to develop and embed tools to detect malice within the systems themselves, and to design effective ways to enhance their safety online. This seminar was intended to bring together researchers from synergistic research communities, including experts working on information and system security on one hand, and those with expertise in human/economic/sociological factors of security on the other. More specifically, in the field of cybersafety, there exist a number of interconnected, complex issues that cannot be addressed in isolation, but have to be tackled and countered together. Moreover, it is necessary for these challenges to be studied under a multi-disciplinary light. Consequently, we identified and focused on the most relevant issues in cybersafety, and explored both current and emerging solutions. Specifically, we discussed four problems that are the most pressing both in terms of negative impact and potential danger on individuals and society, and challenging open research problems requiring a multi-disciplinary approach: Cyberbullying & Hate Speech, CyberFraud & Scams, Reputation Manipulation & Fake Activities, and Propaganda. Overall, the seminar was organized to include a number of long talks from senior experts in the field, covering the four main topics
Keywords: Cybersafety; Online Social Networks; Security and Privacy; Legal and Ethical Issues on the Web